Whole Genome Analysis of Lactobacillus plantarum Strains Isolated From Kimchi and Determination of Probiotic Properties to Treat Mucosal Infections by Candida albicans and Gardnerella vaginalis - Beck, Bo Ram; Park, Gun-Seok; Lee, Yong Hyun; Im, Sunghoon; Jeong, Do Yeun; Kang, Jihee (Frontiers in Microbiology, 2019)
Three Lactobacillus plantarum strains ATG-K2, ATG-K6, and ATG-K8 were isolated from Kimchi, a Korean traditional fermented food, and their probiotic potentials were examined. All three strains were free of antibiotic resistance, hemolysis, and biogenic amine production and therefore assumed to be safe, as supported by whole genome analyses. These strains demonstrated several basic probiotic functions including a wide range of antibacterial activity, bile salt hydrolase activity, hydrogen peroxide production, and heat resistance at 70°C for 60 seconds. Further studies of antimicrobial activities against Candida albicans and Gardnerella vaginalis revealed growth inhibitory effects from culture supernatants, coaggregation effects, and killing effects of the three probiotic strains, with better efficacy toward C. albicans. In vitro treatment of bacterial lysates of the probiotic strains to the RAW264.7 murine macrophage cell line resulted in innate immunity enhancement via IL-6 and TNF-α production without lipopolysaccharide (LPS) treatment and anti-inflammatory effects via significantly increased production of IL-10 when co-treated with LPS. However, the degree of probiotic effect was different for each strain as the highest TNF-α and the lowest IL-10 production by the RAW264.7 cell were observed in the K8 lysate treated group compared to the K2 and K6 lysate treated groups, which may be related to genomic differences such as chromosome size (K2: 3,034,884 bp, K6: 3,205,672 bp, K8: 3,221,272 bp), plasmid numbers (K2: 3, K6 and K8: 1), or total gene numbers (K2: 3,114, K6: 3,178, K8: 3,186). Although more correlative inspections to connect genomic information and biological functions are needed, genomic analyses of the three strains revealed distinct genomic compositions of each strain. Also, this finding suggests genome level analysis may be required to accurately identify microorganisms. Nevertheless, L. plantarum ATG-K2, ATG-K6, and ATG-K8 demonstrated their potential as probiotics for mucosal health improvement in both microbial and immunological contexts.